Pengembangan Keterampilan Digital melalui Implementasi Platform Pembelajaran Inklusif RS-BPBL© pada Kelompok Anak Yatim Piatu Duafa - Wahyudi; Karfindo; Monanda Rio Meta; Aulia Ahmad Zakki; Ridwan Ajwari (Forum Kerjasama Pendidikan Tinggi, 2024)
This program aims to enhance inclusive education access for underprivileged orphaned children (AYPD) through the implementation of the RS-BPBL© digital platform at Masjid As-Salaam. The program consists of five stages: socialization, digital literacy training, technology implementation, mentoring, and sustainability. The results show an improvement in participants’ knowledge and interaction during learning, both independently and collaboratively, with an average increase of 84.5% based on pre-test and post-test evaluations. Additionally, participants’ digital skills improved by 85.7%, covering internet navigation, learning application usage, and digital problem-solving. The program also provided educational facilities such as digital devices and internet access, with a service delivery target of 100%. In conclusion, RS-BPBL© has proven effective in bridging the digital education gap among AYPD and significantly empowering them in terms of social inclusion. The program holds potential for replication in other communities with similar challenges.